Paradoxical choice in rats: Subjective valuation and mechanism of choice - Ojeda, A; Murphy, RA; Kacelnik, A (Elsevier, 2018)
Decision-makers benefit from information only when they can use it to guide behavior. However, recent experiments found that pigeons and starlings value information that they cannot use. Here we show that this paradox is also present in rats, and explore the underlying decision process. Subjects chose between two options that delivered food probabilistically after a fixed delay. In one option (“info”), outcomes (food/no-food) were signaled immediately after choice, whereas in the alternative (“non-info”) the outcome was uncertain until the delay lapsed. Rats sacrificed up to 20% potential rewards by preferring the info option, but reversed preference when the cost was 60%. This reversal contrasts with the results found with pigeons and starlings and may reflect species’ differences worth of further investigation. Results are consistent with predictions of the Sequential Choice Model (SCM), that proposes that choices are driven by the mechanisms that control action in sequential encounters. As expected from the SCM, latencies to respond in single-option trials predicted preferences in choice trials, and latencies in choice trials were the same or shorter than in single-option trials. We argue that the congruence of results in distant vertebrates probably reflects evolved adaptations to shared fundamental challenges in nature, and that the apparently paradoxical overvaluing of information is not sub-optimal as has been claimed, even though its functional significance is not yet understood.